Design of monitoring network and determination of water quality variables in Kucuk Menderes River - Gundogdu, V; Ozkan, E Y (Su ürünleri dergisi, 2006)
In order to use water resources efficiently and to plan water usage for different purposes, water quality should be known as well as its quantity. The observation of instantaneous and continuous variations in water quality and determination of natural and human effects are possible only with a conscious and systematic quality measurement network. Formation of a measurement network is a subject on which many scientists are still studying, and for a country like Turkey where measurement stations are newly established, it has a great importance. In this study, a systematic monitoring network was designed in whole Kucuk Menderes River Basin and the water quality of the river was determined according to the pollutants. Thus; definitions and solutions that will make contribution to the management and sustainability of Kucuk Menderes River Basin, were developed.